WAYS TO USE ARTIFICIAL INTELLIGENCE CORRECTLY TO OVERCOME PROBLEMS IN LANGUAGE LEARNING IN THE ERA OF TECHNOLOGICAL GLOBALIZATION AND IMPLEMENT IT TO THE LEARNING PROCESS (SCIENCE TIME JOURNAL, 2026)
In today’s globalized educational landscape, artificial intelligence (AI) is transforming the way foreign languages are learned and taught. The integration of AI into language education offers personalized learning experiences, adaptive feedback, and interactive practice that enhance learner engagement and proficiency. This study examines the effective use of AI in the language learning process, proposing a Human–AI Synergistic Model that combines adaptive technology with teacher guidance and ethical oversight. The model emphasizes diagnostic assessment, individualized practice, communicative simulation, and pedagogical regulation to maximize learning outcomes while fostering learner autonomy, motivation, and ethical awareness. Empirical findings indicate that studentswho engage with AI-supported instruction demonstrate significant improvement in productive skills, reduced speaking anxiety, and greater self-regulated learning compared to traditional instruction methods. Additionally, the research highlights innovative strategies for integrating AI into daily learning routines, offering practical guidance for educators and learners. This study contributes both theoretical and practical insights into how AI can be leveraged responsibly to enhance language acquisition in higher education contexts, preparing learners for participation in an interconnected global environment.